Class, nation, and identity : the anthropology of political movements - Pratt, Jeff C. (Pluto Press, 2003)
Political movements across the world have such diverse characteristics and aims that it is difficult to examine them as a collective group. Movements that are class-based are usually portrayed as formed by economic categories of people driven by material interests. By contrast the study of ethnic or nationalist movements has concentrated on the complexities of identity formation within culturally defined groups driven by strong passions. In this unusual book, Jeff Pratt argues for the need to set up a new analytical framework that extends the study of identity formation, and the ethnographic analysis of economic and social processes, to all political movements. Setting up a new analytical framework, he argues that political processes involve two linked components: a 'discourse' (an identity narrative which positions us within social history) and a 'movement' (the process of organization whereby local social divisions are transformed by their incorporation into a wider movement). He illustrates his arguments with a vivid mix of case studies from across the last century including Basque nationalism, Andalusian anarchism, Italian communism, the break-up of Yugoslavia, to the 'newer' political movements in Europe, in French Occitania and the Italian Lega Nord.
Keywords: Nationalism.; Social classes -- Political aspects.; Nationalism -- Europe -- Case studies.; Europe -- Social conditions.; Nationalisme.; Classes sociales -- Aspect politique.; Nationalisme -- Europe -- Études de cas.; Europe -- Conditions sociales.; nationalism.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Nationalism; Social classes -- Political aspects; Social conditions; Europe; Sociale klassen.; Case studies; Case studies.; Études de cas.